Morphology effects of bismuth catalysts on electroreduction of carbon dioxide into formate. (10th May 2019) - Gao, Tengfei; Wen, Xuemei; Xie, Tianhui; Han, Nana; Sun, Kai; Han, Lu; Wang, Hangchao; Zhang, Ying; Kuang, Yun; Sun, Xiaoming
Abstract: A study of understanding the effect of morphology during the electrochemical CO2 reduction on bismuth catalysts is presented. Three types of pristine bismuth catalysts with designed morphologies were synthesized via the hydrothermal method and their catalytic activity and selectivity towards electrochemical CO2 reduction were analyzed and discussed. In comparison with bismuth nanowires and nanospheres, two-dimensional bismuth nanosheets with a thickness of 10 nm show enhanced selectivity for formate formation due to the highest (012) facet texture coefficient value. The highest Faradaic efficiency of 85% for the formation of formate was achieved at −0.85 V vs. RHE and a stability electrolysis test conducted at the same potential showed only 8% activity loss over 8 h. These results reveal the importance of the nanoengineering strategy for developing the next generation of non-precious metal electrocatalyst for CO2 reduction. Highlights: Bi nanospheres, nanowires and nanosheets were prepared to understand the structure-activity relationship. The highest Faradaic efficiency of 85% for formate was achieved using Bi nanosheets. Bi nanosheets possess thinner sheet structure and more (012) plane exposure.